ANALYSIS OF INPUT AND IMPACT INDICATORS OF THE SPHERE OF HIGHER EDUCATION OF BELARUS (EDUCATION IN THE 21ST CENTURY, 2023)
Effective management approaches to higher education rise the challanges which have to respond adequately to the demands of modern society. Over time, it becomes clear that challenges in society are not just about finding specific solutions to specific nations and states. These solutions become futile if there is no common logic at the international level. That is why the nations and states considered the solution of challenges a common priority and their solutions began to be promoted through unification and finding common solutions. An example of such a union is the EAEU, member-states of which raise field issues and seek common solutions.The field of education requires interconnected solutions, which is necessary to study the peculiarities of education management in the EAEU member-countries: the possibilities of a united confrontation of a possible challenge. In this study, the peculiarities of higher education management in Belarus, as one of the EAEU member-countries, are presented.The history of various unions in other countries shows that in the joint strategic programs of the EAEU member-countries, over time, economic issues and their solutions will bring the need for closer cooperation in education and, in particular, in its management, and educational cooperation will play a key role in solving economic problems.At present, we can state that effective cooperation between the EAEU member-countries makes it actual the dissemination of value and cultural atmosphere, which will be common not only for economic and political institutions, but also for the societies of our countries. And this is possible only through the education system, because the education system is the only social institution that not only creates and transmits values and cultural perceptions and expectations, but can also disseminate them in society. And as the life experience shows, legal norms are established in the legal field, but their dissemination in the society is realized and becomes possible due to the transfer of generations in the education system and the creation of a common cultural environment.The aim of this study is to identify, with a specially developed methodology, the features of the input and impact indicatores of Belarusian higher education field as the EAEU member-country.Within the framework of the research, a new methodology of comparative analysis of higher education systems of EAEU member-country was developed and introduced, within the framework of which for the first time indicators of input and impact were brought out, due to which it is possible not only to argue but also to evaluate and analyze the peculiarities.
Keywords: Keywords: Higher education, EAEU member-country, Belarusian education system, investment indicators, input indicatores, impact indicators.